Pendampingan Pasien Obesitas dan Diabetes Mellitus Era Pandemi Covid-19 - Niken Wahyu Aryanti; Yustiana Olfah; Tri Siswati (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
This activity aims to provide community service with the One Student One Family (OSOF) scheme. The activity was carried out to improve the quality of patients with obesity and Diabetes mellitus (DM) in Family A (families with problems with non-communicable diseases or PTM) in Bantul, Yogyakarta during the Covid-19 pandemic. The methods used in this service are education, mentoring, monitoring, and evaluating consumption patterns, physical activity, measuring weight, and checking blood sugar levels. In addition, the commitment of patients and family members is initiated to achieve a good quality of life. The results of this service activity indicate that mentoring impacts improving the quality of life of patients in the form of improving diet, exercise habits/physical activity, weight loss of 1.1 kg in 2 weeks, and decreasing blood sugar levels by 116 mg/DL. In addition, there is a patient's commitment to implementing a healthy lifestyle vigorously in the long term to produce better results. Family members also expressed a commitment to continuously provide motivation, support, and an environment to improve the patient's quality of life. This proves that the OSOF program has succeeded in having a positive impact on the target.